"Perfil de enfermedades bucales y necesidad de tratamiento en escolares de 6, 12, 15 años en instituciones educativas privadas del distrito de Cajamarca, 2016 - Armas Calderón, Marina Mercedes (2017)
ABSTRACT Objective: The purpose of this study was to determine the prevalence and necessity of treatment in relation to oral diseases in schoolchildren aged 6, 12 and 15 years old in I. Private of the District of Cajamarca. Method: This descriptive, stratified cross-sectional study included a sample of 309 schoolchildren, proportionally according to the population: 101, 6-year-olds, 78, 12-year-olds, 130, 15-year-olds from a total of nine private schools . To evaluate the prevalence, the indexes of dental status WHO, CPITN, IMO-OMS were used, using a clinical form. Results: The prevalence of dental caries for schoolchildren aged 6 years old was 30.47%. The predominant genus is male, with 33.66%, which is statistically significant at p <0.05. The prevalence of dental caries for schoolchildren aged 12 years old in deciduous teeth was with 50% and in permanent teeth was of 15.09%. The predominant genus is female with 21.24%, being statistically highly significant with a p <0.0001. The prevalence of dental caries for schoolchildren aged 15 years old was with 12.90%. There was no significant statistical difference between genders p> 0.05. The prevalence of periodontal status (blennding, calculus) in schoolchildren aged 12 and 15 years was: 48.54% and 47.24%, respectively. The predominant gender is male in both cases. In the statistical analysis it determined that there is significant difference between genders.> 0.05 The prevalence of malocclusion for schoolchildren aged 12 and 15 years old was of 88.75% and 62.59%, respectively, in terms of gender, there was no statistically significant difference. . Conclusions: It is concluded that 6-year-old schoolchildren have a prevalence of dental status (30.47%) and 12- and 15-year-olds have a prevalence (15.09%, 12.90%). The prevalence of periodontal status in schoolchildren aged 12 and 15 years was of: 48.54% and 47.24%, respectively. The prevalence of malocclusion for schoolchildren aged 12 and 15 years was of: 88.75% and 62.59%, respectively. The need for treatment for dental status was sealant, followed by sealing a surface and filling of 2 surfaces or more. The need for treatment for periodontal status was Education in oral health followed by oral education plus prophylaxis.